2020
DOI: 10.1186/s40902-020-00272-5
|View full text |Cite
|
Sign up to set email alerts
|

3D-printed titanium implant with pre-mounted dental implants for mandible reconstruction: a case report

Abstract: Background: This clinical case presented a novel method of segmental mandible reconstruction using 3D-printed titanium implant with pre-mounted dental implants that was planned to rehabilitate occlusion. Case presentation: A 53-year-old male who suffered osteoradionecrosis due to the radiation after squamous cell carcinoma resection. The 3D-printed titanium implant with pre-mounted dental implant fixtures was simulated and fabricated with selective laser melting method. The implant was successfully inserted, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 10 publications
0
33
0
Order By: Relevance
“…When comparing the titanium implants only, the use of 3D printed custom-made implants resulted in more satisfactory results than the use of pre-curved titanium mesh implants, which are more useful in treatment of smaller cranial defects (48,49). Due to their mechanical stability and satisfactory cosmetic results, custom made titanium implants can also be used in the treatment of bone defects after craniofacial or maxillofacial skeleton resections (50,51) or compound injuries, which may be especially diffi cult to reconstruct (52,53). Also, titanium miniplates became a routine mean of cranial bone fl ap fi xation (54), replacing osteosuture and achieving satisfactory results (54) including a reduced osteolysis and complication rate (25).…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the titanium implants only, the use of 3D printed custom-made implants resulted in more satisfactory results than the use of pre-curved titanium mesh implants, which are more useful in treatment of smaller cranial defects (48,49). Due to their mechanical stability and satisfactory cosmetic results, custom made titanium implants can also be used in the treatment of bone defects after craniofacial or maxillofacial skeleton resections (50,51) or compound injuries, which may be especially diffi cult to reconstruct (52,53). Also, titanium miniplates became a routine mean of cranial bone fl ap fi xation (54), replacing osteosuture and achieving satisfactory results (54) including a reduced osteolysis and complication rate (25).…”
Section: Discussionmentioning
confidence: 99%
“…They reported a 100% survival rate of these implants at a one-year follow-up with minimum complications [ 160 ]. Park et al (2020) reported a case in which a 3D printed implant was placed in a patient with an atrophic mandible due to osteoradionecrosis who received radiation treatment post squamous cell carcinoma resection [ 165 ]. Their results revealed that 3D printed implants with a pre-mounted dental implant resulted in a better mandibular function [ 165 ].…”
Section: 3d Printing In Dental Implantologymentioning
confidence: 99%
“…Further, the mechanical strength of these materials, evaluated via both in vitro and in vivo studies, is on par with natural bone and dental tissues, which makes them the most common implant materials (Li J. et al, 2020). However, these materials undergo degradation during interaction with the biological fluids, leading to corrosion and wear, which can be deposited in the surrounding cells or tissues and cause inflammation (Apaza-Bedoya et al, 2017;Park et al, 2020). Furthermore, osteoporosis, immunocompromised patients of diabetes [3.89% of failure rate (Chrcanovic et al, 2014)], Acquired Immunodeficiency Syndrome (AIDS) condition [10% of failure rate (May et al, 2016)], smoking and radiotherapy in head and neck cancers are the factors that can lead to dental implant failures (Bazli et al, 2020).…”
Section: Conventional Dental Implants and Their Limitationsmentioning
confidence: 99%
“…Generally, titanium and its alloys, such as nitinol were used as a common and successful materials for dental implant applications (Shah et al, 2019). However, these materials are identified to undergo corrosion and wear, which can lead to degradation into their ionic state, deposition in the surrounding tissues and inflammation (Park et al, 2020).…”
Section: Introductionmentioning
confidence: 99%